MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT(TGT) BERBANTU MEDIA CARD SORT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA SD - Wiwik Okta Susilawati; Nesa Nurhalimah; Raimon Efendi (STKIP Subang, 2025)
The background of this research is the low student learning outcomes caused bythe lack of variety in learning methods and the minimal use of interactive media inthe learning process. This study aims to determine the effect of the cooperativelearning model type Teams Games Tournament (TGT) assisted by Card Sortmedia on the learning outcomes of Pancasila Education among fourth-gradestudents at SDN 14 Sitiung. This study used a quantitative approach with a quasi-experimental design in the form of a Nonequivalent Control Group Design. Thesample consisted of two classes: an experimental class and a control class. Thedata collection instrument was a multiple-choice test. The results of the Wilcoxontest analysis showed a significance value of <0.001 (p < 0.05), indicating that thenull hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) wasaccepted. Thus, there is a significant effect of using the TGT model assisted byCard Sort media on students learning outcomes in Pancasila Education. Thismodel effectively enhances students’ active participation and understanding ofconceptual material.